Non-uniform dystrophin re-expression after CRISPR-mediated exon excision in the dystrophin/utrophin double-knockout mouse model of DMD - Britt Hanson; Sofia Stenler; Nina Ahlskog; Katarzyna Chwalenia; Nenad Svrzikapa; Anna M.L. Coenen-Stass; Marc S. Weinberg; Matthew J.A. Wood; Thomas C. Roberts (Elsevier, 2022)
Duchenne muscular dystrophy (DMD) is the most prevalent inherited myopathy affecting children, caused by genetic loss of the gene encoding the dystrophin protein. Here we have investigated the use of the Staphylococcus aureus CRISPR-Cas9 system and a double-cut strategy, delivered using a pair of adeno-associated virus serotype 9 (AAV9) vectors, for dystrophin restoration in the severely affected dystrophin/utrophin double-knockout (dKO) mouse. Single guide RNAs were designed to excise Dmd exon 23, with flanking intronic regions repaired by non-homologous end joining. Exon 23 deletion was confirmed at the DNA level by PCR and Sanger sequencing, and at the RNA level by RT-qPCR. Restoration of dystrophin protein expression was demonstrated by western blot and immunofluorescence staining in mice treated via either intraperitoneal or intravenous routes of delivery. Dystrophin restoration was most effective in the diaphragm, where a maximum of 5.7% of wild-type dystrophin expression was observed. CRISPR treatment was insufficient to extend lifespan in the dKO mouse, and dystrophin was expressed in a within-fiber patchy manner in skeletal muscle tissues. Further analysis revealed a plethora of non-productive DNA repair events, including AAV genome integration at the CRISPR cut sites. This study highlights potential challenges for the successful development of CRISPR therapies in the context of DMD.